EFEKTIVITAS PENINGKATAN AKTIFITAS FUNGSIONAL DENGAN INTERVENSI ICE MASSAGE DAN TERAPI LATIHAN PADA KASUS PLANTAR FASCIITIS (Lembaga Penerbitan Universitas Esa Unggul, 2021)
Plantar fasciitis occurs due to excessive stretching of the plantar fascia which can lead to inflammation of the plantar fascia dimedial calcaneus. The purpose of this study was to analyze the effectiveness of increasing functional activity with ice massage interventions and exercise therapy in cases of plantar fasciitis. This research method is pure experimental with randomized pre-test and post-test group design. In this study 9 respondents as group I were given ice massage intervention and 9 respondents as group II were given exercise therapy intervention. Physical examination of physiotherapy and measurement of increased functional activity were performed using the foot and ankle disability index (FADI). The test results showed an increase in functional activity with exercise therapy intervention before and after treatment in groups using non-parametric tests with the Wilcoxon Signed Ranks Test because the normality value was before P> 0.05 and the value after intervention was P <0.05 data with p = 0.008 (p <0.05), it means that there is a difference before and after treatment in this group. The conclusion in this study is that the effectiveness of increasing functional activity with exercise therapy interventions is better than giving ice massage in cases of plantar fasciitis which can be seen from the mean difference between the ice massage group 15.11 + 4.81 and the exercise therapy group 29.11 + 10.07.